Gay's Self-Acceptance Process on HIV Positive Status - Popy Apri Yanti; Dhesi Ari Astuti (Indonesian Journal of Global Health Research, 2021)
Men with a homosexual orientation are more likely to experience depression than women who have a homosexual orientation. The purpose of this study was to conclude and examine the literatures related to the process of self-acceptance of Gays who were HIV positive. The method used was literature review by searching indexed articles from several database sources such as from PubMed, Proquest Disbursement of databases, scanning, and screening. In the search for the articles, 832 articles were identified. In addition, after filtering the titles, abstracts, and research methods, 103 articles were obtained to be taken and reviewed independently based on the inclusion and exclusion criteria. Then, a further article screening was carried out to find accurate and complete references regarding the self-acceptance process for ga MSM who were HIV positive and obtained 10 articles for a critical appraisal. The author filtered the articles based on the critical appraisal results and obtained 4 articles for a final review based on the period of 2013 to 2018, and identified using an electronic database.The findings showed the process of self-acceptance of gay people who are HIV positive. The responses when they first found out that they were HIV positive mostly showed the same response, namely experiencing anxiety, shock, distrust and rejection of the HIV test results in the form stress and depression. Over time, the informants accepted themselves as HIV positive sufferers in a resigned and strong form. Most of them had not disclosed their HIV status, especially to their partners and families because they were afraid of rejection and stigma.